KADAR MILK UREA NITROGEN (MUN) PADA SAPI PERANAKAN FRIESIAN HOLSTEIN (PFH) BERDASARKAN CALVING INTERVAL YANG BERBEDA - Pratama, Hanif Sabekti; Mustofa, Imam; Lokapirnasari, Widya Paramita; Srianto, Pudji; Rimayanti, Rimayanti; Utama, Suzanita (Ovozoa: Journal of Animal Reproduction, 2019)
Milk urea nitrogen (MUN) analys may be used as a signal potential problem in feeding program. The aim of this research was to know levels of milk urea nitrogen with different calving interval. This research was using purposive sampling in KUD Tani Wilis, Sendang, Tulungagung. The sample was obtained from breeder as much as 16 samples, grouped into 2 groups, group 1 calving interval â‰¤370 and group 2 calving interval â‰¥450. This samples tested in Surabaya laboratory of health (Balai Besar Laboratorium Kesehatan Surabaya). The result showed that MUN not signifcanly different with different calving interval (p>0,05). The conclusion of this research was MUN did not related with different calving interval.